Haematology and serum biochemistry results for anaesthetised northern brown bandicoots (Isoodon macrourus) in south east Queensland. Issue 9 (24th June 2021) - Langhorne, C; McMichael, L; Hoy, J; Kopp, S; Murray, P
Abstract : Bandicoots are terrestrial marsupials, endemic to Australia and Papua New Guinea. Despite drastic declines in several bandicoot species since European settlement, the northern brown bandicoot ( Isoodon macrourus ) remains common in many areas of Australia. It inhabits native environments as well as anthropogenic landscapes. This study presents comprehensive haematologic and serum biochemical results for 39 anaesthetised, clinically healthy, wild‐caught, adult northern brown bandicoots in south east Queensland, Australia. The bloodwork profile of a single animal with chronic prostatic abscessation highlights that haematology and clinical chemistry can provide useful biomarkers for identifying clinical disease in bandicoots. Comparisons of haematologic and biochemical values between sexes of the northern brown bandicoot revealed significant differences for eosinophils, alkaline phosphatase and total bilirubin. At the individual animal level, the ranges established in this study are a guide for monitoring health and disease status; however, they also have much wider applications in population health and ecological research.